(untitled) (Journal of Bangladesh Institute of Planners, 2013)
Community management requires ongoing support from an overseeing institution for sustainable development. In case of rural community management in Bangladesh, it is found that implementation agencies shift responsibilities to beneficiaries achieving the convenient concept of community management model without establishing appropriate local management committee. On the other hand, beneficiaries cannot develop the sense of responsibility because of legal, ownership, or community constraints. On this position, this paper will see practices of Bangladesh government projects for rural community development. Following practicing in the community development field, this paper will assess the community management pointing out the problems related to implementation agencies and beneficiaries. Finally, it will focus on solution for radical change needed if community management systems are to be sustainable. Secondary sources are used to develop this paper where data are analyzed through article review. Vol. 6, December 2013, pp. 87-92